Pengembangan Sistem Berbasis Web pada Bisnis Jasa Seni Lukis - Hugo Ghally Imanaka; Muhammad Tanzil Furqon; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The painting service business is a business that provides the creation of fine art in the form of paintings. Zona Karikatur, Dokter Desain, and Creative are a few examples of digital painting services providers in Indonesia. In their development, these companies find problems in several things such as production processing, ordering, suitability of customer demand, and financial data collection. Therefore, a web for painting service business management was created to help and overcome problems such as managing the order processing, production, and financial data collection to make it more efficient. Waterfall model and object-oriented approach was chosen to build this system. Requirement analysis of this research produces 5 actors, 52 functional requirements, and 1 nonfunctional requirement. This system has been tested using unit testing, integration testing, validation testing, and compatibility testing. Unit testing and integration testing use the whitebox testing techniques, and those have valid results. The implementation of program code on this system uses the Go language. Validation testing uses the blackbox testing technique and it has a validity percentage of 100%. Compatibility testing was carried out using the Crossbrowsertesting tool, it shows that the system can run well on various browsers and devices. Despite this, it has a fatal problem with Internet Explorer 11. Through this development, it produces a system that can manage the painting service business.